Causes of the decrease in income and rent during the pandemic, in the urban transport companies of Juliaca, 2021 - Mamani Quispe, Cristhian Barsen (2023)
The health crisis caused by the coronavirus brought with it endless catastrophes in the country's economy, and in the different economic sectors, among them is the transportation sector, which was hit hard during the pandemic. In this article, a general report of the transport companies must be reconciled, detailing which were the main causes that affected urban transport; and the influence it had on the income of these entities during the COVID-19 pandemic, for this purpose the exploratory level was achieved with a qualitative approach, assisted with the analysis of feelings of polarity and subjectivity, supported by the interview with subject matter experts. The results obtained in the council of the report show that the repercussion of the health crisis was negative, indicating a decrease in income, this was supported by the results obtained in the sentiment analysis, the fears reflected in the results obtained are the fear of contagion, both of users and workers, which greatly affects the work and the habitual development of the public transport service; this was one of the main sources of massive contagion. The fear of fines for lack of implementation of the biosafety protocols was also one of the limitations that had a negative impact on the income of carriers, and consequently, income and rent were greatly affected by these events.